2010
DOI: 10.1108/00346651011015953
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the quality, content, and context of breakfast consumption

Abstract: Abstract.Purpose: Consumption of breakfast is often associated with important health related behaviours. For example, skipping breakfast is related to obesity and eating breakfast is also correlated to cognitive, behavioural, and affective components. This paper attempts to review the breakfast eating literature, and investigate the circumstances under which people consume breakfast, what is actually being consumed, and how much breakfast is eaten therefore Method/Approach: This systematic review summarised th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 29 publications
5
41
0
2
Order By: Relevance
“…These options were further collapsed into three categories, “Never”, “Sometimes” (which included “1-2 times in a week,” “3-4 times in a week,” and “5-6 times in a week”) and “Daily” during analysis. This representation of breakfast consumption is consistent with prior studies [45]. …”
Section: Methodssupporting
confidence: 92%
“…These options were further collapsed into three categories, “Never”, “Sometimes” (which included “1-2 times in a week,” “3-4 times in a week,” and “5-6 times in a week”) and “Daily” during analysis. This representation of breakfast consumption is consistent with prior studies [45]. …”
Section: Methodssupporting
confidence: 92%
“…Although a variety of schools were contacted from various regions, the majority of participants were from high SES backgrounds and Caucasian ethnicity. Breakfast consumption is known to vary according to sociodemographic factors -such that breakfast skipping is higher in lower SES groups (Mullan & Singh, 2010). The relative sociodemographic homogeneity of the current sample may limit the extent to which findings from this study can be generalised to other populations.…”
Section: Strengths and Limitationsmentioning
confidence: 59%
“…25 Consumption of fruits and vegetables, dietary fat, and juice were not associated with obesity as measured via bMi or percent body fat. Although some studies have found that consumption of fruits and vegetables, dietary fat, and juice were related to obesity in children, the results are inconsistent.…”
Section: Resultsmentioning
confidence: 92%